Significance of Using Indigenous Toys and Games in Early Years: A Child’s Way to Learn and Grow - Soni, Romila (THE PRIMARY TEACHER, 2022)
Play-based pedagogy using toys is the most appropriate and preferred pedagogy at the foundational stage. Much of the research endorsed play as fulfilling an important role in early learning. Researchers agree that language, literacy and early numeracy develop in the first six years of a child’s life. High-quality play with developmentally appropriate toys and play materials can really help children fully develop their language, literacy and numeracy skills. All kinds of play experiences build the baby’s brain. Toys provide pleasure and huge fun to the world of children of all stages, only the complexity level of toys get increased according to the age, development and abilities of the children/student. Unlike the fancy, expensive and electronic toys sold in stores today, traditional Indian toys and games are just simple, easy to develop even by the teachers and take their inspiration from the environment. Without doubt, traditional building toys are excellent for a child’s overall development and specifically their language, literacy and early math development. The effect is even greater when teachers and parents are aware of the opportunities for learning which exist in these toys and educational play materials.